Korelasi Status Sosial Ekonomi Rumah Tangga Terhadap Perilaku Hidup Bersih Dan Sehat Di Kelurahan Meranti Pandak Kecamatan Rumbai Kota Pekanbaru - Ramadanti, Sindi Suci; Nurhamlin, Nurhamlin (Peneliti.net, 2025)
This st..udy was c.ond..ucted in Meranti Pandak Village, R..umbai District, Pekanbar..u City. This st..udy aims t.o determine the c.orrelati.on between h.o..useh.old s.oci.o-ec.on.omic stat..us and clean and healthy living behavi.or in Meranti Pandak Village, R..umbai District, Pekanbar..u City. This st..udy ..uses an inferential q..uantitative meth.od with descriptive analysis. This st..udy ..uses a sampling techniq..ue, namely Accidental Sampling with a t.otal .of 97 resp.ondents. Data c.ollecti.on was carried .o..ut by .observati.on, str..uct..ured interviews ..using q..uesti.onnaires, and d.oc..umentati.on. The res..ults .of the st..udy .obtained the level .of h.o..useh.old s.oci.o-ec.on.omic stat..us c.onditi.ons in Meranti Pandak Village, R..umbai District, Pekanbar..u City, the maj.ority .of the p.op..ulati.on is at a m.oderate level, namely 46.19%, m.ost resp.ondents have relatively adeq..uate c.onditi.ons, b.oth in terms .of w.ork, ed..ucati.on, inc.ome, h.ome .ownership, and residence, b..ut there are still s.ome wh.o need m.ore attenti.on t.o impr.ove their welfare. Implementati.on .of clean and healthy living behavi.or in h.o..useh.olds in Meranti Pandak Village, R..umbai District, Pekanbar..u City is 37%, Madya healthy, 32% P..urnama healthy, 24% Independent Healthy and 7% Pratama healthy. The c.orrelati.on between S.oci.oec.on.omic and PHBS is 0.49. This sh.ows that the c.ontrib..uti.on .of S.oci.oec.on.omic c.orrelati.on t.o PHBS is 49%.